Indicative diagnostics of the educational component of human capital based on mathematical modeling - D. Orekhov, Viktor; S. Prichina, Olga; V. Blinnikova, Alla; A. Panfilova, Elena; S. Shchennikova, Elena (Opción, 2019)
The purpose of the research is to develop an indicative diagnostic system for the educational component of human capital based on a mathematical model of the dependence of the gross domestic product at purchasing power parity of different countries on the level of education of workers. The work shows that indicative diagnostics of the human capital educational component, as a basic factor of economic dynamics, provides a satisfactory accuracy of gross domes- tic product calculations, which is characterized by a relative standard error of 9% for the seven largest economies. The article defines the coefficients of contribution to the gross domestic product of various groups of workers by education and confirms that they depend exponentially on the number of years of education. A system of indicative diagnostics of the human capital educatio- nal component is proposed.